Transcriptional Analysis of Maize Leaf Tissue Treated With Seaweed Extract Under Drought Stress - Trivedi, Khanjan; Gopalakrishnan, Vijay Anand K.; Kumar, Ranjeet; Ghosh, Arup (Frontiers in Sustainable Food Systems, 2021)
Kappaphycus alvarezii seaweed extract (KSWE) has been known for its plant biostimulant and stress alleviation activities on various crops. However, very few reports are available depicting its impact at the molecular level, which is crucial in identifying the mechanism of action of KSWE on plants. Here, maize leaf tissue of control and KSWE treated plants were analyzed for their transcriptional changes under drought stress. KSWE was applied foliarly at the V5 stage of maize crop under drought and leaf transcriptome analysis was performed. It was found that total of 380 and 631 genes were up- and down- regulated, respectively due to the application of KSWE. Genes involved in nitrate transportation, signal transmission, photosynthesis, transmembrane transport of various ions, glycogen and starch biosynthetic processes were found up-regulated in KSWE treated plants. While genes involved in the catabolism of polysaccharide molecules such as starch as well as cell wall macromolecules like chitin and protein degradation were found down-regulated. An overview of differentially expressed genes involved in metabolic as well as regulatory processes in KSWE treated plant was also analyzed via Mapman tool. Phytohormone signaling genes such as cytokinin-independent 1 (involved in cytokine signal transduction), Ent-kaurene synthase and GA20 oxidase (involved in gibberellin synthesis) and gene of 2-oxoglutarate-dependent dioxygenase enzyme activity (involved in ethylene synthesis) were found up-regulated while 9-cis-epoxycarotenoid dioxygenase (a gene involved in abscisic acid synthesis) was found down regulated due to the application of KSWE. Modulation of gene expressions in maize leaf tissue in response to KSWE treatment elucidate mechanisms to ward off drought stress which can be extended to understand similar phenomenon in other crops as well. . This molecular knowledge can be utilized to make the use of KSWE more efficient and sustainable.